Perbandingan Nilai Moral Novel Ananta Prahadi dan Ivanna Van Dijk Karya Risa Saraswati - Inda Puspita Sari; Tiya Handayani; Rika Berlista (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to describe the comparison of moral values ​​in the novel Ivanna Van Dijk by RisaSaraswati with the moral values ​​of the novel AnantaPrahadi by RisaSaraswati. The research method uses descriptive qualitative method. The data in this study were obtained by reading, recording and concluding techniques. After the data is collected, data reduction is then performed. The selected data are then classified for further analysis of similarities and differences to be compared until the conclusion of the research results. The results of this study indicate that there are differences and similarities in the moral values ​​of human relations with oneself, human relations with humans, and human relations with God. Comparison of the moral values ​​of the two novels from the aspect of moral values ​​there are differences. In the novel AnantaPrahadi by RisaSaraswati the moral values ​​of human relations with oneself are 19 quotations, human relationships with humans there are 50 quotations, human relationships with God are 8, and the total of these quotations is 149 quotations. Whereas in Ivanna Van Dijk's novel the moral value of human relations with oneself is 26 quotations, human relationships with humans there are 49 quotations, human relationships with God there are 3 quotations, and the total of these quotations is 105 quotations. Conclusion, the comparison of moral values ​​in the two novels is on the number of citations, while the equation lies in the form of quotations of moral values, which dominates the moral values ​​of relationships with others. In addition, the form of expressing the moral values ​​of the two novels is slightly different, namely the implied and explicit meaning. Keywords: Comparison, Novel, Moral Value